2017
DOI: 10.1051/0004-6361/201628962
|View full text |Cite
|
Sign up to set email alerts
|

Globules and pillars in Cygnus X

Abstract: Globules and pillars, impressively revealed by the Spitzer and Herschel satellites, for example, are pervasive features found in regions of massive star formation. Studying their embedded stellar populations can provide an excellent laboratory to test theories of triggered star formation and the features that it may imprint on the stellar aggregates resulting from it. We studied the globule IRAS 20319+3958 in Cygnus X by means of visible and near-infrared imaging and spectroscopy, complemented with mid-infrare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…In any case, we confirm the conclusion from Djupvik et al ( 2017) that the emission distribution of H 2 indicates that the sources of ionisation are the B stars of the embedded aggregate, rather than the external UV field caused by the O-stars of Cyg OB2. We note that another line of evidence in Djupvik et al (2017) showed that the visible spectrum of the H II region is that of a soft ionising radiation, typical of an early-B star. In Sect.…”
Section: Comparison To H 2 Emission and Small-scale Dynamics Of [C Ii] Emissionmentioning
confidence: 66%
See 4 more Smart Citations
“…In any case, we confirm the conclusion from Djupvik et al ( 2017) that the emission distribution of H 2 indicates that the sources of ionisation are the B stars of the embedded aggregate, rather than the external UV field caused by the O-stars of Cyg OB2. We note that another line of evidence in Djupvik et al (2017) showed that the visible spectrum of the H II region is that of a soft ionising radiation, typical of an early-B star. In Sect.…”
Section: Comparison To H 2 Emission and Small-scale Dynamics Of [C Ii] Emissionmentioning
confidence: 66%
“…Earlier studies reported nine cluster members within a projected radius of ∼0.5 pc (Kronberger et al 2006;Kumar et al 2006) and two visible stars had been estimated to have mid-B spectral types (Cohen et al 1989). The scenario of embedded stars was further explored in Djupvik et al (2017), where we found that the globule contains an embedded aggregate of about 30-40 young stellar objects within one arcmin (or 0.4 pc with the adopted distance of 1.4 kpc). Based on the high ratio of Class I to Class II objects, the small cluster was estimated to have an age <1 Myr.…”
Section: Multiwavelengths Observations Of the Globulementioning
confidence: 74%
See 3 more Smart Citations